2013 Update of the 2011 American College of Rheumatology Recommendations for the Treatment of Juvenile Idiopathic Arthritis - Sarah Ringold; Pamela F. Weiss; Timothy Beukelman; Esi Morgan DeWitt; Norman T. Ilowite; Yukiko Kimura; Ronald M. Laxer; Daniel J. Lovell; Peter A. Nigrovic; Angela Byun Robinson; Richard K. Vehe (Современная ревматология, 2014)
Guidelines and recommendations developed and/or endorsed by the American College of Rheumatology (ACR) are intended to provide guidance for particular patterns of practice and not to dictate the care of a particular patient.The ACR considers adherence to these guidelines and recommendations to be voluntary, with the ultimate determination regarding their application to be made by the physician in light of each patient’s individual circumstances.Guidelines and recommendations are intended to promote beneficial or desirable outcomes but cannot guarantee any specific outcome. Guidelines and recommendations developed or endorsed by the ACR are subject to periodic revision as warranted by the evolution of medical knowledge, technology, and practice.The American College of Rheumatology is an independent, professional, medical and scientific society which does not guarantee, warrant, or endorse any commercial product or service.